Financial Distress and Corporate Performance - OPLER, TIM C.; TITMAN, SHERIDAN (Journal of Finance, 1994)
Abstract This study finds that highly leveraged firms lose substantial market share to their more conservatively financed competitors in industry downturns. Specifically, firms in the top leverage decile in industries that experience output contractions see their sales decline by 26 percent more than do firms in the bottom leverage decile. A similar decline takes place in the market value of equity. These findings are consistent with the view that the indirect costs of financial distress are significant and positive. Consistent with the theory that firms with specialized products are especially vulnerable to financial distress, we find that highly leveraged firms that engage in research and development suffer the most in economically distressed periods. We also find that the adverse consequences of leverage are more pronounced in concentrated industries.